Factores críticos para la implementación exitosa de sistemas de gestión de calidad ISO 9001:2015 en el Nivel Medio Superior de la UANL. - González, Jesus Solis; Martínez, Juan Rositas; Codina, José Nicolás Barragán (Revista Daena: International Journal of Good Conscience)
In the present article it is maintained that, although there is a predisposition for higher level institutions to be certified under the ISO 9001: 2015 standard, the effectiveness of these systems as an administrative management tool continues to be questioned today. An objective of this research is to analyze the level of adequacy of management systems ISO- 9001 requirements regarding the quality information in the processes. This research is descriptive, quantitative, not experimental and correlational. This type of study aims to understand the degree of association that exists between two or more concepts, categories or variables in a particular context. An instrument with closed and mixed questions was applied, preceded of invitation letter, objective of the survey, respondent subject, questions and general data. The validity of the instruments was determined with Cronbach's alpha and a simple regression analysis was performed.